The Effect of Foreign Exchange Accumulation on Macroeconomic Stability in Post-Liberalized South Africa - Nkabinde, S'phephelo (Graduate School of Business (GSB), 2021)
This study examines the impact of foreign exchange reserve accumulation on macroeconomic stability in South Africa over the period 1995-2016 using a vector error correction model. The results show that foreign exchange reserve accumulation has a positive impact on macroeconomic stability.